Metagenomic Insights Into Competition Between Denitrification and Dissimilatory Nitrate Reduction to Ammonia Within One-Stage and Two-Stage Partial-Nitritation Anammox Bioreactor Configurations - Bryson, Samuel J.; Hunt, Kristopher A.; Stahl, David A.; Winkler, Mari-Karoliina H. (Frontiers in Microbiology, 2022)
Anaerobic ammonia oxidizing bacteria (Anammox) are implemented in high-efficiency wastewater treatment systems operated in two general configurations; one-stage systems combine aerobic ammonia oxidizing bacteria (AOB) and Anammox within a single aerated reactor, whereas two-stage configurations separate these processes into discrete tanks. Within both configurations heterotrophic populations that perform denitrification or dissimilatory nitrate reduction to ammonia (DNRA) compete for carbon and nitrate or nitrite and can impact reactor performance because DNRA retains nitrogen in the system. Therefore, it is important to understand how selective pressures imposed by one-stage and two-stage reactor configurations impact the microbial community structure and associated nitrogen transforming functions. We performed 16S rRNA gene and metagenomic sequencing on different biomass fractions (granules, flocs, and suspended biomass) sampled from two facilities treating sludge dewatering centrate: a one-stage treatment facility (Chambers Creek. Tacoma, WA) and a two-stage system (Rotterdam, Netherlands). Similar microbial populations were identified across the different samples, but relative abundances differed between reactor configurations and biomass sources. Analysis of metagenome assembled genomes (MAGs) indicated different lifestyles for abundant heterotrophic populations. Acidobacteria, Bacteroidetes, and Chloroflexi MAGs had varying capacity for DNRA and denitrification. Acidobacteria MAGs possessed high numbers of glycosyl hydrolases and glycosyl transferases indicating a role in biomass degredation. Ignavibacteria and Phycosphaerae MAGs contributed to the greater relative abundance of DNRA associated nrf genes in the two-stage granules and contained genomic features suggesting a preference for an anoxic or microoxic niche. In the one-stage granules a MAG assigned to Burkholderiales accounted for much of the abundant denitrification genes and had genomic features, including the potential for autotrophic denitrification using reduced sulfur, that indicate an ability to adapt its physiology to varying redox conditions. Overall, the competition for carbon substrates between denitrifying and DNRA performing heterotrophs may be impacted by configuration specific selective pressures. In one-stage systems oxygen availability in the bulk liquid and the oxygen gradient within granules would provide a greater niche space for heterotrophic populations capable of utilizing both oxygen and nitrate or nitrite as terminal electron acceptors, compared to two-stage systems where a homogeneous anoxic environment would favor heterotrophic populations primarily adapted to anaerobic metabolism.